HuR regulates telomerase activity through TERC methylation - Hao Tang (Nature Portfolio, 2018)
Mutations in the RNA component TERC can cause telomerase dysfunction but the underlying mechanisms are largely unknown. Here, the authors show that RNA-binding protein HuR regulates telomerase function by enhancing the methylation of TERC, which is impaired by several disease-relevant TERC mutations.